Anestésicos volátiles en oxigenadores durante la circulación extracorpórea. - Gutiérrez-Soriano, Laura; Kling-Gómez, Juan Carlos; Becerra-Zapata, Eduardo; Quintero, Olga; Maya-Trujillo, Nicolás; Peña-Blanco, Laura (Colombian Journal of Anesthesiology / Revista Colombiana de Anestesiología)
Introduction: Continuous monitoring of exhaled concentrations and CO levels is often lacking during the administration of inhaled anesthetics in cardiopulmonary bypass (CPB), these levels often being adjusted intermittently based on blood gas values. This approach disregards variations in fresh gas and circulatory flows between blood samples. Objective: To assess gas behavior during bypass circulation, evaluate data reliability, and analyze gradients through the membrane oxygenator. Methods: Real-time monitoring of inhaled and exhaled volatile anesthetics, CO, and oxygen was conducted at the oxygenator inlet and outlet ports during CPB. Seventy adult patients undergoing cardiac surgery on CPB were included in order to analyze the impact of circulatory flow across different oxygenators. Results: A strong correlation was found between end-tidal CO and arterial blood gas CO (Spearman’s Rho = 0.74, p = 0.00). Isoflurane gradients differed significantly among the Affinity, Fusion, and Terumo oxygenators (p = 0.015). Equilibrium for Isoflurane was reached in 493.9 ± 164.98 seconds (95% CI: 454–532 seconds). When circulatory flow was reduced to 0.5 L/min, exhaled concentrations increased significantly (Fisher’s T, p = 0.07). Sevoflurane washout varied significantly across oxygenators at CPB initiation (mean: 117.5 s). Conclusions: Continuous monitoring of inhaled and exhaled gases during CPB should be mandatory to optimize anesthetic delivery and achieve targeted plasma concentrations.